Towards the development of an intuitive teleoperation system for human support robot using a VR device. (1st October 2020) - Nakanishi, Jun; Itadera, Shunki; Aoyama, Tadayoshi; Hasegawa, Yasuhisa
Abstract : This paper presents our development of an intuitive teleoperation system for Toyota's Human Support Robot. While this robot has been widely used as an autonomous agent in the field of service robotics, we explore a possibility of this robot for the use of remote assistance of daily activities in home environments. For rapid prototyping an affordable teleoperation system, we adopt a commercially available VR device as a user interface and develop a Robot Operating System (ROS)-based control framework building on the software application programming interfaces (APIs). In particular, we implement a singularity robust inverse kinematics algorithm to achieve a coordinated whole-body motion of the robot for safe and intuitive operation. We empirically evaluate the practical feasibility of the proposed teleoperation system through various test tasks. We discuss the potential and limitations of the current development for its future improvement. GRAPHICAL ABSTRACT: UF0001